Invariance Analysis, Exact Solution and Conservation Laws of (2+1) Dim Fractional Kadomtsev-Petviashvili (KP) System - Kumar, Sachin; Kour, Baljinder; Yao, Shao-Wen; İnç, Mustafa; Osman, Mohamed S. (Mdpi, 2021)
In this work, a Lie group reduction for a (2 + 1) dimensional fractional Kadomtsev-Petviashvili (KP) system is determined by using the Lie symmetry method with Riemann Liouville derivative. After reducing the system into a two-dimensional nonlinear fractional partial differential system (NLFPDEs), the power series (PS) method is applied to obtain the exact solution. Further the obtained power series solution is analyzed for convergence. Then, using the new conservation theorem with a generalized Noether's operator, the conservation laws of the KP system are obtained.
Keywords: fractional Kadomtsev-Petviashvili system; lie group analysis; power series solutions; convergence analysis; conservation laws